Studies on Design Parameters for Linseed Crop Thresher - Ramteke, Anil S; Sirohi, NPS (Journal of Agricultural Engineering, 2003)
Experimental studies were conducted to determine the design parameters, namely, crop, moisture content, cylinder speed, cylinder concave clearance and threshing mechanism for the threshing of linseed crop. Threshing efficiency was found to increase at higher cylinder speed and reduced concave clearance for both the threshing mechanisms i.e. rasp bar and spike tooth. Grain damage was found to be in inverse relation with crop moisture and concave clearance but in direct relation with the cylinder speed. The energy consumption increased with the increase in the cylinder speed and moisture content of the crop. Recommended values of cylinder speed, moisture content and concave clearance were in the range of 15-20 m/s, 8-10 % and 5 -7.5 mm, respectively. Among the two threshing mechanisms, rasp-bar mechanism was found to be more effective.